2021
DOI: 10.18357/jcs463202120026
|View full text |Cite
|
Sign up to set email alerts
|

We Are All In This Together: Supporting Hearts and Minds During Unprecedented Times

Abstract: This article discusses the potential that trauma-informed pedagogy and social-emotional learning practices hold for supporting educators during the COVID-19 pandemic and beyond. The authors bring a critical lens to considering these approaches, noting some limitations and provisos in their use. We advocate for dialogue, mentorship, and professional learning in using them not only to support educators but to authentically include diverse ways of knowing, doing, and being in early childhood environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Students who have strong relationships with grownups at school can find ways to self-regulate and cope more effectively, which will lead to benefits. Community events and opportunities for relationship work have an overall benefit, as seen by this study and others like Koslouski and Stark (2021) and Hudson and Huston (2021). The study participants communicated that their relationships with students and taking time to improve those relationships were always worthwhile.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Students who have strong relationships with grownups at school can find ways to self-regulate and cope more effectively, which will lead to benefits. Community events and opportunities for relationship work have an overall benefit, as seen by this study and others like Koslouski and Stark (2021) and Hudson and Huston (2021). The study participants communicated that their relationships with students and taking time to improve those relationships were always worthwhile.…”
Section: Discussionmentioning
confidence: 58%
“…TIP at this site engaged teachers in reflective practice, which according to other studies like Anderson et al (2021), Chafouleous (2021), andBrunzell et al (2018), is a necessary skill. Teachers shared experiences that built on their capacity to manage the needs that come with student backgrounds and new experiences that are happening in a post-COVID world (Hudson & Huston, 2021;Taylor, 2021;Wharton-Beck et al, 2022). The research in these two cycles revealed that talking about student needs and situations with other educators helped reassure educators that they were not alone and that others understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations